2016
DOI: 10.3399/bjgp16x685213
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine and z-hypnotic prescribing for older people in primary care: a cross-sectional population-based study

Abstract: Background Overall prescribing of benzodiazepines and z-hypnotics (B&Zs) has slowly reduced over the past 20 years. However, long-term prescribing still occurs, particularly among older people, and this is at odds with prescribing guidance.  Aim To compare prescribing of B&Zs between care home and non-care home residents ≥65 years old.  Design and setting Cross-sectional population-based study in primary care in Scotland.  Method National patient-level B&Z prescribing data, for all adults aged ≥65 years, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 27 publications
1
30
1
3
Order By: Relevance
“…A recently published Swiss study using claims data found no association between use and the risk of Alzheimer’s disease,31 contrary to previous evidence 32. In other countries the prevalence of benzodiazepine use in the elderly population ranged from 15% to 31% 1 6 33–35. In our study, about 20% of enrollees received at least one benzodiazepine prescription in 2017, with two-thirds of them receiving the equivalent of 30 DDD or more, and 80% with estimated treatment durations longer than 2 weeks.…”
Section: Discussioncontrasting
confidence: 96%
“…A recently published Swiss study using claims data found no association between use and the risk of Alzheimer’s disease,31 contrary to previous evidence 32. In other countries the prevalence of benzodiazepine use in the elderly population ranged from 15% to 31% 1 6 33–35. In our study, about 20% of enrollees received at least one benzodiazepine prescription in 2017, with two-thirds of them receiving the equivalent of 30 DDD or more, and 80% with estimated treatment durations longer than 2 weeks.…”
Section: Discussioncontrasting
confidence: 96%
“…These consequences affected older patients, which are those who received off-label prescriptions most frequently in our study. Probably, this is a shared problem with other countries like Italy, where a study conducted in pharmacies showed that 80% of those who took benzodiazepines did so during more than one year [34], and elderly patients were the citizens that were most exposed to this risk [35]. In the United States, prescription and long-term (> 12 months) prescription use were more frequent in women and the elderly (14-32%) [36].…”
Section: Discussionmentioning
confidence: 99%
“…Medical practitioners must recognize the additional risk of PIMs in patients with polypharmacy, and are recommended to carefully evaluate each medication to determine if it is essential to the patient's well‐being in order to reduce the burden of PIMs and polypharmacy. It would likely be effective to focus on BZA, as BZA prescriptions are common in primary care settings, and previous research in Japan also showed that frequently prescribed PIMs were BZA . BZA in older persons are commonly used, and have been associated with falls, hip fractures, cognitive impairment and ED visits .…”
Section: Discussionmentioning
confidence: 99%